Potassium aluminium sulphate (Alum) inhibits growth of human axillary malodor producing skin flora in vitro - Hassanain Al-Talib; Nur Izzati Syamimi Mohd Nasir; Hafizuddin Yaziz; Nur Fatihah Zulkafli; Nur Aqidah Adani; Ahmad Ikhwan Noor Rashidi; Chandrika Murugaiah; Syahrul Azlin Shaari (Universiti Teknologi MARA, 2016)
Introduction: Axillary malodor is caused by microbial biotransformation of non-smelling molecules present in apocrine secretions, into volatile odorous molecules. This study aimed to determine the antimicrobial activities of potassium aluminium salts (alum) against four malodor-producing axillary bacterial flora, as an alternative natural product for reducing axillary malodor.